Scattering journeys, regenerative environments. A material ecocritical reading of the diasporic storyworld in Shaun Tan’s refugee graphic novel The Arrival - Sofia Cavalcanti (MediAzioni)
Pushed out of time, place, and history, refugees are typically imagined as humanitarian subjects whose lives are marked by exclusion and constitutive otherness. Thought of as objects of pity, but also as disrupters of an established order, forcibly displaced people are imprinted by a logic of compassion, passivity, and aberration. Literature, however, provides an alternative site for the representation of refugeedom as an empowering experience that enables the formulation of a different sense of self as well as creative human-environmental interactions. This article will focus on the locations where such interactions take place by examining the foreign cityscape in Shaun Tan’s refugee graphic novel The Arrival (2006). Unlike traditional representations of the new land as a place of loss, dispersal, and powerlessness, Tan’s illustrations portray the host city as both a tangible and imagined space of diversity, where inter- and intra-specific interactions play a crucial role in the protagonist’s physical and personal journey. Through a material ecocritical lens, the article examines how the matter of the book, both living and non-living, tells a story of successful adaptation and home building thanks to the protagonist’s capacity to establish a sense of intimacy with the nonhuman world that surrounds him. In conclusion, the apparently unhomely city portrayed by Tan is ultimately the setting of an alter-tale, that is, an alternative narrative in which the interrelationship between the refugee and the material entities that inhabit the land of arrival opens up unexpected possibilities for the displaced to experience not much the scattering as the regenerative potential of refugeedom.